MALJUT Mobiliario para micro apartamentos (2024)
Degree project focused on furniture design multifunctional to optimize monospaces in micro apartments in Bogotá, improving the housing experience of users in these spaces. The goal is to create furniture multifunctional that creates dynamic environments considering daily activities and reduce the furniture saturation. This type of housing responds to a new lifestyle adopted by new generations that prefer spaces compact. However, the lack of furniture suitable for these spaces generates problems of habitability. This project seeks to innovate in the Colombian furniture industry, creating proposals that redefine the perception of living through furniture, incorporating multifunctionality to improve the habitability of the micro apartments, analyzing the context, the user and temporality to design multifunctional furniture that converts small spaces into environments practical and habitable.